RETRACTED: Jabbar et al. Sinapic Acid Attenuate Liver Injury by Modulating Antioxidant Activity and Inflammatory Cytokines in Thioacetamide-Induced Liver Cirrhosis in Rats. Biomedicines 2023, 11, 1447 - Ahmed A. J. Jabbar; Zaenah Zuhair Alamri; Mahmood Ameen Abdulla; Ahmed S. AlRashdi; Soran Kayfi Najmaldin; Mustafa AbdulMonam Zainel (Biomedicines)
The journal retracts the article titled “Sinapic Acid Attenuate Liver Injury by Modulating Antioxidant Activity and Inflammatory Cytokines in Thioacetamide-Induced Liver Cirrhosis in Rats” [...]